Solidification and stabilization of mercury-contaminated tailings in artisanal and small-scale gold mining using tras soil - Ranno Marlany Rachman; Uniadi Mangidi; Yulinah Trihadiningrum (Brawijaya University, 2023)
Artisanal and small-scale gold is known to be sources of mercury pollution. This mercury contamination occurs when gold is isolated by the amalgamation method, contamination occurs. Mercury pollution in small-scale artisanal gold mining in the Kulon Progo area of Yogyakarta, the lowest tailing content was 164.49 mg kg-1, and the highest was 383.21 mg kg-1. This value exceeded the quality standard stipulated by Indonesian Government Regulation 22 of 2021 of 75 mg kg-1. The technology that can control pollution is stabilization/solidification (S/S). This research aimed to determine the optimum composition of the tailings mixture with tras soil. Variations in the design of tras soil with tailings were 100:0, 90:10, 80:20, 70:30, 60:40, 50:50, 40:60, 30:70, 20:80, and 10:90. The results showed that the optimum tras: tailings soil composition was 90:10, with a compressive test of 31 t m-2. Toxicity Characteristic Leaching Procedure (TCLP) was 0.0033 mg L-1 according to the quality standard of Indonesian Government Regulation no. 22, 2021, with a value of 0.05 mg L-1. The compressive strength results follow the quality of the US EPA of 35 t m-2.